The story goes like this - Silverstein, Carolyn, author; Altschul, Andrew, advisor; McConigley, Nina, committee member; Brady, Tracy, committee member (Colorado State University. Libraries, 2025)
"The Story Goes Like This" is an upmarket contemporary novel exploring mental illness, familial drama, sexuality, and memory.